KUALITAS PELAYANAN MEETING PACKAGE TERHADAP KEPUASAN PELANGGAN DI NOVOTEL BALI NGURAH RAI AIRPORT - Ratri Paramitha; Ni Nyoman Nia Arisandi; Ketut Arjaya (Journal of Event and Convention Management, 2022)
MICE (Meeting, Incentive, Conference, Exhibition) is a type of tourism that is currently promising business, especially in Bali. Many hotels in Bali provide and offers meeting venues with various advantages to potential customers. Service quality is the key to achieve customer satisfaction. Customer satisfaction is characterized by overall satisfaction, willingness to recommend, and interest in repeat purchases. The phenomenon that occurs at Novotel Bali Ngurah Rai Airport is there are complaints from customers who held meetings in 2017-2020. This research aims to determine the quality of meeting package services on customer satisfaction at Novotel Bali Ngurah Rai Airport by using five dimensions of service quality as a reference, there are tangible, reliability, responsiveness, assurance, and caring. The technique for determining the sample is using a saturated sampling technique which makes the entire population a sample, there are 98 respondents who have held meetings at Novotel Bali Ngurah Rai Airport. The data analysis technique used in this study is a quantitative data technique whose data was obtained through a questionnaire and tested for validity and reliability with the help of the SPSS version 26 program and then analyzed using a Likert scale. The results of data processing with the title of meeting package services on customer satisfaction at Novotel Bali Ngurah Rai Airport obtained an average value of 3.83 which means good.